Effectiveness of a peer-to-peer, self-management intervention for young people with depression and anxiety in Denmark: an observational study and a propensity score-matched comparison - Andersen, Susan; Thygesen, Lau Caspar; Jensen, Marie Pil; Lauridsen, Sigurd; Folker, Anna Paldam; Nielsen, Maj Britt Dahl (Frontiers in Public Health, 2024)
Objective: This study investigated the effectiveness of a 7-weeks peer-to-peer program for young people aged 15 to 25 years with depression or anxiety symptoms in Denmark. Methods: A total of 483 participants (72% women) participated in the program and the evaluation. The participants completed questionnaires at baseline, postintervention, and at 5-month follow-up to assess changes in depression symptoms (using Beck´s Depression Inventory-II), anxiety symptoms (using Spielbergers State-Trait Anxiety Inventory for Adults) and self-efficacy in controlling or managing the illness (using the personal control subscale from the Illness Perception Questionnaire-Revised). Analyses were done using repeated measures mixed linear regression models. Moreover, a register-based matched comparison group was derived as a comparison to assess changes in being in education and employment at 8-month follow-up. Results: Within the intervention group, both depression and anxiety scores declined across the 5-month follow-up compared to baseline (b=-9.6, 95% CI: -11.2, -8.1 for depression symptoms). The self-efficacy score increased from baseline to post-intervention (b=1.4, 95% CI: 1.0, 1.8) and this level was maintained at follow-up. More than half of the participants were in education at baseline while 24% received social transfer payments. Compared with matched comparison group, a lower proportion of the intervention group remaining in education (71% vs 80%). Among participants who were employed at baseline, a higher proportion of the intervention group were enrolled in education (27% vs 19%) and were unemployed (14% vs 4%) compared to the matched comparison group. Conclusion: This study supports the effectiveness of a peer-to-peer intervention for depression and anxiety symptoms, and self-efficacy in symptom control. However, mixed effects on education and employment were observed, indicating a negative impact on education among those initially enrolled and a higher proportion of employed participants starting education.